Methodological Strategies to Listen to Children's Voices: A Systematic Critical Review - Angel Urbina-Garcia (Universidad Pedagógica Nacional, 2019)
This article reports a systematic review of educational research relating to the most common methodological strategies used by researchers to listen to children's voices. We followed the EPPI-centre approach (2007) to identify what the most widely used methodological strategies are, in order to listen to the voice of 3 to 7 years olds children. Our review identified 210 empirical studies from peer-reviewed journals written in English and Spanish between 2015 and 2018, of which, only 34 studies met the inclusion criteria for this study. Findings revealed that adult-led interviews and adult-led observations were the most common methodological strategies to listen to children's voices followed by group discussions to a lesser extent. We found limited evidence of studies using hands-on activities where children were given the power to decide how to, and what type of information they wanted to express (i.e., school child-led tours), however these strategies did not prevail in the literature reviewed. Issues of adult-child power imbalances were identified -arguably posing challenges to listen to children's voices. These findings have implications for policy, practice and research internationally.